Risk Analysis of Musculoskeletal Disorders (MSDS) Among Fresh Fruit Bunch (FFB) Loaders at PT. XYZ - Arsi, Fadli; Nasirly, Riri; Rahmat, Nuraini; Fachri Nasution; Hutasoit, Lidya Septriana (Journal of Engineering Science and Technology Management, 2025)
This study aims to identify the risk of musculoskeletal disorders (MsDs) among fresh fruit bunch (FFB) loading workers at Afdeling 6 of PT. XYZ, Pelalawan. A quantitative approach was used with the Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) as research instruments. The NBM results indicated that the most frequently reported discomfort was in the back, upper arms, wrists, and legs. Meanwhile, the REBA assessment showed that all workers fell into the high-risk category with scores ranging from 8 to 9, indicating the need for immediate changes in work methods. These findings suggest that manual FFB loading activities pose a significant risk of work-related injuries. Therefore, improvements in working posture, the use of ergonomic tools, and better work schedule arrangements are necessary to reduce the risk of muscle injuries among workers..